The Impact of Mobile JKN Application Registration Service Quality on Patient Satisfaction at Jenggawah Community Health Center, Jember Regency - Sofiana Sofiana; Yusita Titi Hapsari; Hanif Hadinata Utama (JURNAL ADMINISTRASI & MANAJEMEN, 2025)
This study examines the effect of registration service quality via the Mobile JKN application on patient satisfaction at Jenggawah Public Health Center, Jember Regency. The Mobile JKN app, developed by BPJS Kesehatan, aims to improve healthcare access through digital innovation: however, challenges remain, especially for elderly users or those with limited digital literacy. Using a quantitative survey method, data were collected from 109 patients who used the app, focusing on five service quality dimensions (reliability, responsiveness, empathy, tangibles, assurance) and four satisfaction indicators (ease of use, service speed, information quality, user comfort). The results of multiple linear regression show that reliability, tangibles, and assurance significantly affect patient satisfaction, while responsiveness and empathy do not. The model explains 77.6% of the variation in satisfaction (Adjusted R² sama dengan 0.776), suggesting that system reliability, clarity, and usability are critical to patient satisfaction in digital health services. These findings also underscore the importance of enhancing digital inclusion to ensure equitable access to health innovations.